1989
DOI: 10.1042/bj2580853
|View full text |Cite
|
Sign up to set email alerts
|

A 13C-n.m.r. investigation of the ionizations within an inhibitor–α-chymotrypsin complex. Evidence that both α-chymotrypsin and trypsin stabilize a hemiketal oxyanion by similar mechanisms

Abstract: 13C-n.m.r. was used to investigate the structure of the inhibitor enzyme complex formed when alpha-chymotrypsin is alkylated by L-1-chloro-4-phenyl-3-tosylamido-[2-13C]butan-2-one. Two signals are detected. The one at 204.82 +/- 0.11 p.p.m. does not titrate from pH 3 to 9 and is assigned to alkylated methionine-192. The second signal titrates from 99.08 p.p.m. to 103.44 p.p.m. with pKa 8.67. This signal is assigned to a tetrahedral adduct formed between the hydroxy group of serine-195 and the inhibitor. The ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(108 citation statements)
references
References 41 publications
5
103
0
Order By: Relevance
“…Spectra were recorded at 25°C. Chemical shifts in aqueous media were referenced to tetramethylsilane at 0 ppm as described previously [32]. Data were processed with no zero filling using Bruker WINNMR software and exponential multiplications with 2 Hz line broadening were carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Spectra were recorded at 25°C. Chemical shifts in aqueous media were referenced to tetramethylsilane at 0 ppm as described previously [32]. Data were processed with no zero filling using Bruker WINNMR software and exponential multiplications with 2 Hz line broadening were carried out.…”
Section: Methodsmentioning
confidence: 99%
“…In aqueous solutions the chemical shift of the alpha-carbon of glycine was used as a chemical reference as described previously [14]. The chemical shift d 6 -dimethyl sulphoxide (< 5%…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…Using 13 C-NMR it has been shown that when substrate derived chloromethylketone inhibitors alkylate the active site histidine residue of the serine proteases trypsin [12,13], chymotrypsin [10,11,[14][15][16] and subtilisin [10,11,16] the active site serine hydroxy group reacts with ketone carbon to form a tetrahedral adduct analogous to the catalytic tetrahedral intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitor Synthesis-Z-Ala-Pro-Phe-glyoxal, Z-Ala-ProPhe- [2][3][4][5][6][7][8][9][10][11][12][13] C]glyoxal, Z-Ala-Ala-Phe-glyoxal, Z-Ala-Ala-[1-13 C]Phe-glyoxal, and Z-Ala-Ala-Phe- [2-13 C]glyoxal were synthesized using the methods described by Djurdjevic-Pahl et al (1).…”
Section: Materials-l-[1-mentioning
confidence: 99%